2013
DOI: 10.1371/journal.pone.0078750
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nonhuman Primate Model for Influenza Transmission

Abstract: Studies of influenza transmission are necessary to predict the pandemic potential of emerging influenza viruses. Currently, both ferrets and guinea pigs are used in such studies, but these species are distantly related to humans. Nonhuman primates (NHP) share a close phylogenetic relationship with humans and may provide an enhanced means to model the virological and immunological events in influenza virus transmission. Here, for the first time, it was demonstrated that a human influenza virus isolate can produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…Host species-specific selection on other viral nucleoproteins has been reported, such as that on influenza A virus nucleoprotein, which is restricted by the myxovirus resistance protein A (MxA) differentially in birds, humans, and nonhuman primates (32,33). Polymorphisms in host-specific restriction factors may be one possible mechanism for the diversity we observed in ORF 7 in our study.…”
Section: Discussionmentioning
confidence: 48%
“…Host species-specific selection on other viral nucleoproteins has been reported, such as that on influenza A virus nucleoprotein, which is restricted by the myxovirus resistance protein A (MxA) differentially in birds, humans, and nonhuman primates (32,33). Polymorphisms in host-specific restriction factors may be one possible mechanism for the diversity we observed in ORF 7 in our study.…”
Section: Discussionmentioning
confidence: 48%
“…[120][121][122][123][124][125] Studies on animal models of influenza infection in pregnancy are limited. Here, we focus on studies in mice and nonhuman primate (cynomolgus macaque).…”
Section: Animal Studiesmentioning
confidence: 99%
“…7,8 Other species that may be used to study transmission include (outbred) guinea pigs 7,13 and, as recently identified, the common marmoset. 14 The animal models mentioned in the paragraph above each have their advantages and limitations. It has proven difficult to correlate markers Q5 of cellular immunity with pathogenesis and transmission in these animal species.…”
mentioning
confidence: 99%